B14 High-throughput Gene Expression Analysis Of Human Striatal Nuclei Development In Control And Huntington's Disease Patients. (17th September 2014) - Straccia, M; García, G; Sanders, P; Vinh, N-N; Rosser, A; Canals, JM
Abstract : Huntington's disease (HD) is characterised by specific degeneration of striatal GABAergic medium spiny neurons (MSNs) occurs. Implementation of cell replacement strategies for HD using pluripotent stem cells (PSC) requires development and characterisation of new differentiation protocols since the available protocols are too long and inefficient. This can be partially explained because striatal developmental biology is quiet unknown and based on rodent developmental studies. Our present aim is to establish specific human gene expression profile that can be used for the refinement of MSN differentiation protocols. In this view, we analyse quantitative expression of 112 genes involved in telencephalon development, subpallium specification and striatal maturation in human fetal and adult tissues. We also compare post-mortem caudate and putamen nuclei of control and HD patients in order to establish differential expression gene pattern to be used as baseline in in vitro disease models. Unbiased hierarchical cluster analysis reveals human whole ganglionic eminence (WGE) specific gene expression profile compared to fetal cortex and to adult striatal nuclei. Further analysis show a specific developmental pattern of expression in those genes involved in striatal specification. Expression levels comparison of control human tissues against diseased samples suggests specific pathways impairment. In conclusion, we present a new quantitative dataset which spread new light on human striatal nucleus development at gene expression level. Interestingly, this dataset can be used as a baseline to evaluate the efficiency of available and future differentiation protocols helping refinement and evaluating the effects of modifications when improving. Furthermore, this approach may identify gene expression profiles that reflect HD-specific phenotypes.